Analisis Video Animasi Kampanye Anti Bunuh Diri WHO Tahun 2019 - Rifandary, Dina; Kasmana, Kankan (ARTic, 2024)
Preventing suicide: Information for teachers is a 42-second animated video, publication media for the WHO 2019 anti-suicide campaign, discussing suicide among adolescents is a real and inherent phenomenon in society, through this illustration other important information will be conveyed through animated videos. Against this background, the urgency in this research is to analyze the content of the animated video which contains elements of framing devices (methaphors, catchphrases, exemplars, depictions, and visual images) and reasoning devices (roots, and appeal to principle) based on Gamson and Modiglani's framing theory model. The results of this research can show the visual elements in the animated video that contain elements of framing devices and reasoning devices displayed in the animated video. The benefit of this research is to understand how framing analysis frames or conveys problems by displaying creative visuals that can attract the attention of its target audience.